The bright and dark side of avoidance crafting: How work design matters - Elisa Lopper; Fangfang Zhang; Maria Tims (Journal of Occupational and Organizational Psychology, 2025)
To address the growing challenges in today's workplace, employees may use avoidance crafting to reduce high job demands or avoid situations low in job resources. However, previous research links avoidance crafting positively—rather than negatively—to exhaustion, potentially due to an overemphasis on avoidance behavioural demands crafting, neglecting avoidance cognitive forms and their focus on job demands and resources. This study refers to the hierarchical job crafting conceptualization, distinguishing between behavioural and cognitive changes in job demands and resources, to investigate the links between avoidance crafting dimensions and exhaustion at both between and within-person levels. We also explore the moderating effects of general job autonomy and time pressure. Daily diary data (Nbetween0.167em=0.167em78, Nwithin0.167em=0.167em377) revealed that avoidance cognitive demands crafting was negatively associated with exhaustion at both levels, highlighting that altering perceptions of job demands is more effective than targeting low job resources. Moreover, work design matters: at the day level, avoidance cognitive demands crafting was particularly effective in reducing exhaustion when employees generally faced low job autonomy and high time pressure. These findings emphasize the importance of differentiating avoidance crafting dimensions and suggest that avoidance cognitive demands crafting seems particularly useful in demanding work environments.
Keywords: 650; avoidance crafting; between-person level; exhaustion; within-person level; work design